Efficacy and safety of transcutaneous auricular vagus nerve stimulation for frequent premature ventricular complexes: rationale and design of the TASC-V trial - Yu Liu; Xinyao Wei; Lixin Wang; Yanling Yang; Liya Xu; Tianheng Sun; Li Yang; Song Cai; Xiaojie Liu; Zongshi Qin; Lulu Bin; Shaoxin Sun; et al. (BMC, 2024)
Abstract Background Premature Ventricular Complexes (PVCs) are very common in clinical practice, with frequent PVCs (more than 30 beats per hour) or polymorphic PVCs significantly increasing the risk of mortality. Previous studies have shown that vagus nerve stimulation improves ventricular arrhythmias. Stimulation of the auricular distribution of the vagus nerve has proven to be a simple, safe, and effective method to activate the vagus nerve. Transcutaneous au ricular vagus nerve stimulation (taVNS) has shown promise in both clinical and experimental setting for PVCs; however, high-quality clinical studies are lacking, resulting in insufficient evidence of efficacy. Methods The study is a prospective, randomized, parallel-controlled trial with a 1:1 ratio between the two groups. Patients will be randomized to either the treatment group (taVNS) or the control group (Sham-taVNS) with a 6-week treatment and a subsequent 12-week follow-up period. The primary outcome is the proportion of patients with a ≥ 50% reduction in the number of PVCs monitored by 24-hour Holter. Secondary outcomes include the proportion of patients with a ≥ 75% reduction in PVCs, as well as the changes in premature ventricular beats, total heartbeats, and supraventricular premature beats recorded by 24-hour Holter. Additional assessments compared score changes in PVCs-related symptoms, as well as the score change of self-rating anxiety scale (SAS), self-rating depression scale (SDS), and 36-item short form health survey (SF-36). Discussion The TASC-V trial will help to reveal the efficacy and safety of taVNS for frequent PVCs, offering new clinical evidence for the clinical practice. Trial registration Clinicaltrials.gov: NCT04415203 (Registration Date: May 30, 2020).